Regulation of hypoxia-inducible factor is preserved in the absence of a functioning mitochondrial respiratory chain. - Vaux, E; Metzen, E; Yeates, K; Ratcliffe, P (2001)
Hypoxia-inducible factor (HIF) mediates a large number of transcriptional responses to hypoxia and has an important role in processes that include angiogenesis and erythropoiesis. The HIF DNA binding complex consists of 2 basic-helix-loop-helix PAS proteins designated alpha and beta subunits. Regulation occurs principally through the alpha subunits, which are stabilized and activated in hypoxia. Although substantial evidence implicates reactive oxygen species (ROS) in the regulatory process, the precise mechanisms remain unclear. Mitochondria are an important source of ROS, and in one model it has been proposed that hypoxia increases the generation of ROS at complex III in the mitochondrion and that this signal acts through a transduction pathway to stabilize HIF-1alpha and to activate HIF. To test this model the induction of the HIF-1alpha subunit and the HIF target gene, glucose-transporter-1, was examined in a variety of mutant cells that lacked mitochondrial DNA (rho0) or had other genetic defects in mitochondrial respiration. HIF induction by hypoxia was essentially normal in all cells tested. Hydrogen peroxide production was measured by the luminol/peroxidase method and found to be reduced in rho0 versus wild-type cells and reduced by hypoxia in both rho0 and wild-type cells. Furthermore, concentrations of rotenone that maximally inhibited respiration did not affect HIF activation by hypoxia. These data do not support the model outlined above and indicate that a functional respiratory chain is not necessary for the regulation of HIF by oxygen.